Modeling of Critical Threshold of Preference for Collusion (C.T.P.C.) and Cost Structure in Tunisian Mobile Market - Sami Debbichi; Walid Hichri (PT Mattawang Mediatama Solution, 2024)
We present in this paper a modeling of the critical threshold of preference for collusion (C.T.P.C.) in different market structure using the interconnection fees and their marginal cost, in a Cournot competition. The objective is to compare the preference for collusion regarding this threshold in market structures and within two contexts: linear interconnection costs and quadratic ones. Collusion is more difficult in private duopoly that in a mixed one. This difficulty is increased with linear cost structure than quadratic costs. The findings we obtain from the application of our results to the Tunisian mobile market between (2002-2019) are consistent with our theoretical model.